ENHANCING ENGLISH TEACHERS’ PEDAGOGICAL COMPETENCE THROUGH “REAL ACTION” FEATURES ON THE MERDEKA MENGAJAR PLATFORM (PMM) - Yulanda, Dwistri; Irawan, Nico; Rahayu, Endah Yulia (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2025)
The “Real Action” features within the PMM are designed to bridge the gap between theory and practice. These features encourage teachers to engage in reflective practices, collaborative learning, and continuous professional development. This study employs a descriptive qualitative-methods research design to explore the implementation of “realaction” features in Merdeka Mengajar Platform (PMM) aimed at enhancing English teachers’ pedagogical competence. The qualitative data from interviews and focus group discussions. The participants in this study were English teachers from various educational institutions across East Java, specifically those who are active users of the PMM platform. A total of 200 teachers were selected through a stratified random sampling technique to ensure representation from different areas, school types (public and private), and teaching experience levels. The results of this study indicate that the implementation of “real action” features in Merdeka Mengajar Platform has had a profound impact on enhancing English teachers’ pedagogical competence.